Evaluasi Efektivitas Peran dan Fungsi Audit Inernal (Studi Kasus pada Grup Perusahaan Farmasi Dipa Rajawali) - Sumantri Bratakusuma, SE., M.Ak. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
This research aims to study the process of a paradigm shift or a view of the role and functions of internal audit, the cause of inefficiency function and role of internal audit in risk management, top management support and auditees of the findings of internal audit and process improvement and prevention is done in order to create corporate governance good. The object of research is a group company namely Dipa Eagles Pharmaceutical Group Company which is engaged in the fields of pharmaceuticals and medical devices. The study was conducted using a descriptive approach by comparing the analysis of the facts that occurred in the company's activities between theory and practice. From the results of field studies and literature, indicates that the Eagles Dipa Pharmaceutical Group has made the process of paradigm shift on the role and functions of internal audit of